The Effect of Hippocampal Cognitive Impairment and XIAP on Glucose and Lipids Metabolism in Rats - Chunbo Xia; Lin Zhu; Wenhua Shao; Sisi Mi; Sen Du; Lin Ye; Manjun Liu; YongJun Pang; Linlin Nong; Changwen Jiang; Hailu Zhao; Guangying Qi (Cellular Physiology and Biochemistry, 2016)
Background/Aims: To investigate the effect of cognitive impairment and X-linked inhibitor of apoptosis protein (XIAP) on glucolipid metabolism. Materials and Methods: β-amyloid (Aβ 1-42) was injected into the hippocampus of rats to establish a cognitive impairment model. Trans-activator of transcription (TAT)-XIAP fusion protein (the TAT-XIAP group), PBS (the model group), or XIAP antisense oligonucleotides (the ASODN group) was injected into the lateral ventricles of the rats to increase and decrease the activity of XIAP in the hippocampus. To determine the level of blood glucose and lipids, adenosine monophosphate-activated protein kinase (AMPK) expression of liver and hipppocamual neuronal apoptosis. Results: The levels of FPG, TG, TC and LDL were significantly higher in the TAT-XIAP group, the model group and the ASODN group than in the blank group (P Conclusion: Cognitive impairment and hippocampal neuron apoptosis can cause glucose and lipids metabolic abnormalities, possibly by regulating gastrointestinal motility and AMPK expression in the liver. The changes in the function of XIAP, which is an anti-apoptotic protein in the hippocampus, may affect the metabolism of glucose and lipids.